Analysis of Science Probelm Solving Abilty Reviewed from Student Curiosity and their Learning with E-Module Assisted PjBL Model Respiratory Matter - Temu Temu; YL. Sukestiyarno; AA Ketut Budiastra (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study was to improve students' curiosity and problem-solving skills in science in grade V on respiratory material through a project-based learning model based on e-modules. Data collection techniques used unstructured interviews, questionnaires, tests, and documentation. Data analysis techniques were analyzed using quantitative analysis, namely one-variable t-test, difference test, N-Gain test, and regression test, and then using qualitative analysis. The results of the study: (1) Students' science problem-solving skills are more than the KKM value of 75 with a t-count value of 2.741 (> 1.706) and a significance value of 0.015 (<0.05); (2) There is an increase in science problem-solving skills of 44.27% after learning with the PjBL/project Based Learning model assisted by e-modules; (3) There is an influence of curiosity on science students' problem-solving skills of 84.7% so that it can be concluded that the greater the student's curiosity, the higher the problem-solving skills.